Resilience in migraine brains: decrease of coherence after photic stimulation - Mendoca-de-Souza, Mayara; Monteiro, Ubirakitan M.; Bezerra, Amana S.; Silva-de-Oliveira, Ana Paula; Ventura-da-Silva, Belvania R.; Barbosa, Marcelo S.; Souza, Josiane A.; Criado, Elisângela C.; Ferrarezi, Maria C.; Alencar, Giselly d.; Lins, Otavio G.; Coriolano, Maria d.; et al. (Frontiers in Human Neuroscience, 2012)
Background: During migraine attacks, patients generally have photophobia and phonophobia and seek for environments with less sensorial stimulation. Present work aimed to quantify cortical partial directed coherence (PDC) of electroencephalographic (EEG) recordings from migraine patients and controls in occipital, parietal and frontal areas with or without photic stimulation. Our hypothesis is that migraine patients with visual aura might have neuronal networks with higher coherence than controls even in interictal periods due to a predisposition in sensory cortical processing. Methods: Eleven adult women with migraine with visual aura (at least 48 hours without previous attacks) and seven healthy adult woman were submitted to EEG recording in basal state and during photic stimulation. Results: When compared to healthy volunteers, migraine patients show different coherence profiles. Migraine patients had greater coherence than controls during the basal period (without photic stimulation), showing predisposition for sensory processing in many frequency ranges. After photic stimulation, patients showed a decrease in cortical coherence while controls had an increase. Conclusions: When compared to healty subjects, migraineurs show increased cortical coherence before photic stimulation, but a decrease when stimulation starts. This may be the expression of a resilience mechanism that allows migraineurs the interictal period. The PDC analysis permits to address a patient coherence profile, or “coherence map”, that can be utilized for management of the headache disorder or following up treatments.